2005
DOI: 10.1510/icvts.2004.102673
|View full text |Cite
|
Sign up to set email alerts
|

Does pleurotomy during internal mammary artery harvest increase post-operative pulmonary complications?

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was whether pleurotomy during internal mammary artery (IMA) harvest increases post-operative pulmonary complications. Altogether, 154 papers were found using the reported search, of which 8 presented the best evidence to answer the clinical question. The author, journal, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
1
8
0
1
Order By: Relevance
“…26,27 Consequently, a major incidence of respiratory complications during the postoperative course may occur and delay pulmonary function recovery. 28,29 This may explain our findings. The MOV group, which presented a higher incidence of cough and consequently more thoracic pain, demonstrated a greater impairment in pulmonary function at 24 h after the extubation, as demonstrated by the correlation tests applied in this study.…”
Section: Discussionsupporting
confidence: 56%
“…26,27 Consequently, a major incidence of respiratory complications during the postoperative course may occur and delay pulmonary function recovery. 28,29 This may explain our findings. The MOV group, which presented a higher incidence of cough and consequently more thoracic pain, demonstrated a greater impairment in pulmonary function at 24 h after the extubation, as demonstrated by the correlation tests applied in this study.…”
Section: Discussionsupporting
confidence: 56%
“…There is clear evidence that postoperative pulmonary dysfunction of varying degrees is an inevitable consequence of cardiac surgery [2,3,13]. A number of factors appear to contribute to pulmonary function abnormalities including general anesthesia, median sternotomy, surgical injury and cardiopulmonary bypass [3,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, reports have demonstrated that ITA harvesting during a CABG is an adjunctive factor for further impairment of postoperative pulmonary function, and may increase the risk of pleuropulmonary complications [2,3,13]. Previous reports attributed the postoperative poor lung function to pleurotomy followed by chest tube insertion and additional trauma to the chest wall during dissection of ITA graft [2,5,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, higher levels of FiO 2 during mechanical ventilation because of general anesthesia during surgery are associated with atelectasis formation [27,32]. Another causative factor could be the harvesting of the internal mammary artery [33]. Use of the internal mammary artery graft has been found to be associated with a greater occurrence of post-operative atelectasis.…”
Section: Discussionmentioning
confidence: 99%